2006
DOI: 10.1038/sj.emboj.7601170
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and IL-12 specifically regulate the expression of Rab5 and Rab7 via distinct signaling pathways

Abstract: Recent studies have shown that phagosome maturation depends on the balance between pro-inflammatory and anti-inflammatory cytokines, indicating that cytokine modulates phagosome maturation. However, the mechanism of cytokine-mediated modulation of intracellular trafficking remains to be elucidated. Here, we have shown that treatment of macrophages with IL-6 specifically induce the expression of Rab5 through the activation of extracellular signal-regulated kinase, whereas IL-12 exclusively upregulate the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 48 publications
1
52
1
1
Order By: Relevance
“…Fang et al (48) also reported TLR2-mediated phagocytosis and autophagy through the JNK signaling pathway in macrophages. Another recent study has shown that IL-12-mediated activation of p38 MAPK induces the expression of Rab7 to regulate endocytic trafficking (49). In contrast, our results have shown that TLR2-mediated activation of JNK and ERK induces the expression of Rab7, which facilitates Ag traffic to the late endosome/lysosome for efficient Ag presentation to CD8 + T cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Fang et al (48) also reported TLR2-mediated phagocytosis and autophagy through the JNK signaling pathway in macrophages. Another recent study has shown that IL-12-mediated activation of p38 MAPK induces the expression of Rab7 to regulate endocytic trafficking (49). In contrast, our results have shown that TLR2-mediated activation of JNK and ERK induces the expression of Rab7, which facilitates Ag traffic to the late endosome/lysosome for efficient Ag presentation to CD8 + T cells.…”
Section: Discussioncontrasting
confidence: 54%
“…Cytotoxicity of NK cells in vitro was assessed in a 51 Cr-release assay on YAC-1 target cells. Murine NK-sensitive target cells, YAC-1 (Moloney murine leukemia virus-induced lymphoma cells) as well as NK-insensitive cells, P815 (mastocytoma cells, H-2 d ) were propagated in RPMI 1640 medium additionally supplemented with 8% FBS and 10 g/ml gentamicin (R8 medium) 37°C, 8% C0 2 .…”
Section: Assessment Of Nk Cytotoxicitymentioning
confidence: 99%
“…Furthermore, the pharmacological inhibition of p38 and transfection with p38 siRNA reduces the LPS-induced phagocytosis of GFP-E. coli by RAW264.7 cells (49). Interestingly, IL-12 induces Rab7 expression in J774E cells through the activation of p38 MAPK (51). Under constitutive conditions, p38 can modulate the rate of endocytic traffic by regulating the activity of GDI on Rab proteins (20,50), thereby affecting endocytosis in vivo (50).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that various cytokines and hormones can modify Rab5 and Rab7 availability in murine and human cells (51,(71)(72)(73). The enhanced expression of Rab7 in J774E cells by muramyl-dipeptide has been shown to promote the transport of live Salmonella to lysosomes, preceding efficient killing (74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation